HIF-1α regulates angiogenesis via Notch1/STAT3/ETBR pathway in trophoblastic cells. Issue 24 (17th December 2019) - Yu, Nan; Wu, Jian-Li; Xiao, Juan; Fan, Lei; Chen, Su-Hua; Li, Wei
ABSTRACT: Background: Preeclampsia is a pregnancy-related complication and the major cause to maternal and fetal mortality. Despite extensive studies, the pathogenesis of this disease still remains unknown. Here we explored the roles of HIF-1α and Notch1/ETBR in preeclampsia. Methods: Immunohistochemistry, RT-qPCR and western blot were used to measure levels of Notch1 and ETBR in placentas of preeclampsia patients. Transwell invasion assay and in vitro Matrigel assay were used to test the functions of Notch1, HIF-1α and ETBR in invasion and angiogenesis of trophoblast cells. In addition, we used reduced uterine perfusion pressure (RUPP) rat model to study preeclampsia in vivo . Results: We found that Notch1 and ETBR were down-regulated in the placenta of patients with preeclampsia. Hypoxia promoted invasion and angiogenesis of trophoblast cells, and up-regulated expressions of HIF-1α, Notch1/ETBR. Overexpression of Notch1 facilitated invasion and angiogenesis of trophoblast cells while HIF-1α inhibitor suppressed. Furthermore, Notch1 or ETBR could promote angiogenesis of trophoblast cells in RUPP rats. Conclusions: Our study reveals that HIF-1α and Notch1/ETBR play important roles in preeclampsia. Hypoxia-induced HIF-1αregulated Notch1/ETBR signaling, thereby modulating invasion and angiogenesis of trophoblast cells. These results shed light on molecular mechanisms of preeclampsia and provide potential targets for preeclampsia therapy.